Análise do sucesso/insucesso do estudante surdo no curso técnico em agropecuária do IFPA – Castanhal - SILVA, Antonia Leite da (2022)
This dissertation was written with the objective of making a situational diagnosis of the academic results of deaf students enrolled in the technical course in agriculture and cattle raising of the Federal Institute of Pará – Castanhal Campus and analyze the factors that contributed to success/ unsuccess, as well as to identify the methodologies and the directions adopted by the teachers and institution to ensure educational inclusion and facilitate learning on the school journey. Thus, we opted, methodologically, for a qualitative approach since it is concerned with getting to know the aspects related to the reality of the educational and inclusive process made available to ensure, in addition, their permanence, learning and academic performance for the exercises of their profession. In this context, the data survey was carried out through a bibliographic review of references in educational policies: Amabile (2012), Barufi (2014), Saviani (2018); of the legislation that guide the policies: Lei 9.394/96, Lei 7.853/89, Lei 10.432/2005, Lei 13.146/2015; and inclusion, deaf education and Teacher training: Quadros (2008), Skliar (2013), Muttão and Lodi (2018), Damázio (2007), Mantoan (2015) and Lacerda (2013), Lacerda and Santos (2013), Pacheco et al (2007), Ribeiro and Silva (2016); among other important references to discuss the theme in focus and through electronic questionnaries with structured and semi-structured questions applied to teachers, coordinators, pedagogical staff, Libras interpreter, class representatives Center for Assistance to People with Specific Needs (NAPNE), members and managers and face-to-face interview (ensuring social distance) with semi-structured questionnaire for deaf student and parents/guardians. The data analysis occurred descriptively and interpretatively, after cataloging the collection. Regarding teaching practices for deaf students, it was confirmed that these occur randomly, without specific direction, which evidenced from the end of the research – question proven in the participants‟ answers, the need for resources and training to ensure inclusion and the full development of students, which resulted in the production of na instructional guide with guidelines for planning methodological care, reception and/or accompaniment of these students and a closer look at the specific educational needs of eaf students and even basic guidelines, that many teachers need in order to have a more productive feedback in the teaching-learning process.